Women of Uganda Network - Okello, Dorothy (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Women of Uganda Network (WOUGNET) is a non-governmental organization established in May 2000. WOUGNET promotes the use of ICTs by women to enhance their capacities and opportunities for sharing and exchanging informatio